Plant-Specific Myosin XI, a Molecular Perspective - Tominaga, Motoki; Nakano, Akihiko (Frontiers in Plant Science, 2012)
In eukaryotic cells, organelle movement, positioning, and communications are critical for maintaining cellular functions and are highly regulated by intracellular trafficking. Directional movement of motor proteins along the cytoskeleton is one of the key regulators of such trafficking. Most plants have developed a unique actin–myosin system for intracellular trafficking. Although the composition of myosin motors in angiosperms is limited to plant-specific myosin classes VIII and XI, there are large families of myosins, especially in class XI, suggesting functional diversification among class XI members. However, the molecular properties and regulation of each myosin XI member remains unclear. To achieve a better understanding of the plant-specific actin–myosin system, the characterization of myosin XI members at the molecular level is essential. In the first half of this review, we summarize the molecular properties of tobacco 175-kDa myosin XI, and in the later half, we focus on myosin XI members in Arabidopsis thaliana. Through detailed comparison of the functional domains of these myosins with the functional domain of myosin V, we look for possible diversification in enzymatic and mechanical properties among myosin XI members concomitant with their regulation.